THE DEVELOPMENT OF QUR'AN COMMENTATORS' REQUIREMENTS: FROM THE AFFIRMATIVE ERA TO THE REFORMATIVE ERA - Rozy, Yahya Fathur (Universitas Muhammadiyah Surakarta, 2024)
This research will look at the requirements that must be possessed by Qur'an commentators who have developed in every era. As a limitation, this research focuses on the affirmative era of interpretation (8-15 AD) and reformative era of interpretation (19 AD). The main sources of this research are four books written by commentators representing each era; two commentators from affirmative era of interpretation; Az-Zarkasyi and As-Suyuthi, and two commentators from reformative era of interpretation; Ahmad As-Syurbashi and Quraish Shihab. Using a socio-historical approach, this literature-based qualitative research concludes that there have been developments in the requirements of commentators in each era. From only to require mastering Ulumul Qur'an skills to demand of mastering a set of modern knowledge. All of this cannot be separated from the influence of historical facts on the problems and demands of the times faced by these commentators.